Screening and characterization of lactic acid bacteria and fermentation of gamma-aminobutyric acid-enriched bamboo shoots - Chen, Meilin; Xia, Hongqiu; Zuo, Xifeng; Tang, Danping; Zhou, Haoyu; Huang, Zijun; Guo, Ailing; Lv, Jun (Frontiers in Microbiology, 2024)
In order to produce fermented bamboo shoots with functional properties, two strains of lactic acid bacteria were selected for inoculation and fermentation. One strain, Lactiplantibacillus plantarum R1, exhibited prominent potential probiotic properties (including gastrointestinal condition tolerance, adhesion ability, antimicrobial ability, and antibiotic resistance), while the other, Levilactobacillus brevis R2, demonstrated the capability of high γ-aminobutyric acid (GABA) production (913.99 ± 14.2 mg/L). The synergistic inoculation of both strains during bamboo shoot fermentation led to a remarkable increase in GABA content (382.31 ± 12.17 mg/kg), surpassing that of naturally fermented bamboo shoots by more than 4.5 times and outperforming mono-inoculated fermentation. Simultaneously, the nitrite content was maintained at a safe level (5.96 ± 1.81 mg/kg). Besides, inoculated fermented bamboo shoots exhibited an increased crude fiber content (16.58 ± 0.04 g/100 g) and reduced fat content (0.39 ± 0.02 g/100 g). Sensory evaluation results indicated a high overall acceptability for the synergistically inoculated fermented bamboo shoots. This study may provide a strategy for the safe and rapid fermentation of bamboo shoots and lay the groundwork for the development of functional vegetable products enriched with GABA.